A report on injuries and illnesses among athletes and games officials during XII South Asian Games-2016, Shillong, India - Borgohain, Bhaskar; Tariang, Cherry M.; Darjee, J. P.; Marbaniang, Arnest; Komut, Ozing; Angom, Gangarani; Marak, Robert S.; Khonglah, Tashi G.; Barooah, Rituparna; Momin, Emanual; Suokhrie, Neilatuo U.; Lyngdoh, Nebanshan; et al. (International Journal of Research in Orthopaedics, 2017)
Background: The 12th South Asian Games (SAG) was held from February 5-16, 2016 in Guwahati and Shillong. International level mega-events bring people of different background to a single geographic location after extensive travel. Surveillance and measures for primary and secondary prevention of injuries and illnesses by the organizers and host country is highly desirable. There is no such previous published report on South Asian games. The study was conducted with the aim to analyse the medical arrangements and report injuries and illnesses in athletes and games officials during the South Asian Games-2016 at Shillong venue. Methods: : It is a retrospective study from all daily records of injuries and illnesses reported to the principal referral hospital designated to treat all significant injuries and illnesses for games officials and athletes from all eight participating countries staying in Shillong. Results: Eight major sports were conducted in Shillong that included Badminton, Boxing, Football, Judo, Taekwondo and Wushu. The average age of the injured athletes or ill officials combined was 27.5 years. Male to female ratio was approximately 7:3. There were a total of 65 injuries (59.6%) out of 109 hospital visits including six dislocations involving the upper limbs, but only one athlete required hospitalization. Athletes from three major contact sports namely taekwondo, football and wushu dominated the injured list. A significant number of games officials had injuries and medical illnesses, some requiring hospitalization. Conclusions: Thorough planning for befitting medical care arrangements is indispensable for successful conduct of any major sports event. Significant training, sensitization, preparedness, knowledge-based manpower and infrastructure are needed for adequate medical coverage before, during and after the schedule of any major sports events.